Case Report: Primary intracranial lymphoma and meningioma manifesting as a composite tumor in a cat - Vezza, Christina R.; Southard, Teresa L.; LeRoith, Tanya; Strandberg, Natalia J.; Fowler, Kayla M.; Shinn, Richard L.; Rossmeisl, John H.; Parker, Rell L. (Frontiers in Veterinary Science, 2025)
A 13-year-old, male neutered, Domestic Shorthair cat presented to the Virginia Tech Veterinary Teaching Hospital Neurology service for evaluation of episodes of altered mental status. On initial evaluation, the patient was noted to be alert and responsive, with a vestibular ataxia characterized by falling to the left and circling to the right. The neuroanatomic localization was consistent with multifocal intracranial disease affecting both brainstem and forebrain structures. A brain MRI revealed an extra-axial T2/FLAIR hyperintense, T1 isointense, strongly, homogenously, contrast-enhancing, plaque-like lesion affecting the meninges of the olfactory, frontal, parietal, and temporal areas of both cerebral hemispheres with extension into the falx cerebri and third ventricle. In the left temporal area, the plaque-like lesion was contiguous with a solitary, round, extra-axial, T2/FLAIR hypointense, T1 isointense, strongly and homogenously contrast-enhancing mass lesion. Bilateral caudal transtentorial and foramen magnum herniations were present. The cat’s neurologic status declined, and a left rostrotentorial craniectomy, regional durectomy, and temporal mass resection were performed. Both the meningeal plaque-like lesion and the temporal mass were sampled during surgery. The meningeal lesion presented two distinct neoplastic populations consistent with meningioma and large cell lymphoma, while the temporal mass cells were consistent with a meningothelial meningioma. The patient’s neurologic status improved postoperatively, and the cat was discharged on prednisolone therapy. The cat died 21 days after surgery, and a necropsy was performed. Gross examination revealed a plaque-like meningeal lesion involving the cerebrum. Histopathologically, the dura mater and subarachnoid space were infiltrated by sheets of CD79a-positive large neoplastic round cells, accompanied by numerous non-neoplastic CD3-positive T cells and IBA1-positive histiocytes, consistent with a T-cell-rich large B-cell lymphoma, and whorls of spindle-shaped cells, consistent with a meningioma. This is a rare case of an intracranial composite tumor of meningioma and primary central nervous system (CNS) T-cell-rich large B-cell lymphoma in a cat. Post-treatment survival in this cat was poor, similar to previously reported outcomes in cats with intracranial lymphoma.